LEADERSHIP ATTITUDE AS A DETERMINANT OF EMPLOYEE PERFORMANCE: A CORRELATIONAL STUDY AT PT PERKEBUNAN NUSANTARA I REGIONAL 2, KEBUN SEDEP - Safitri, Novi Rizqia; Kaila Tabina Kurniawan; Harmon (LPPM STIE EKA PRASETYA, 2025)
This study investigates the role of leadership attitudes as a determinant of employee performance at PT Perkebunan Nusantara I Regional 2 Kebun Sedep. A quantitative correlational approach was used, collecting data through structured questionnaires with a Likert scale, distributed to 30 employees. The aim was to assess employee perceptions of leadership behavior and its effects on performance. The findings reveal a strong and positive correlation between leadership attitudes and employee performance. Changes in leadership attitudes are consistently reflected in similar shifts in employee performance, either up or down. Leaders who demonstrate clear, supportive, and motivating behaviors tend to boost employee engagement and overall performance. These leadership traits help create a conducive work environment, thereby contributing to higher employee performance and the organization’s success. This study underscores the importance of leadership attitudes as a fundamental factor in enhancing employee performance. By focusing on leadership development that encourages clarity and motivation, organizations can improve employee efficiency and job outcomes. Based on these results, it is recommended that organizations implement leadership development programs to enhance the leadership qualities that drive positive employee performance. Prioritizing supportive and clear leadership behaviors is crucial for fostering a motivated and productive workforce, which ultimately improves the overall success and productivity of the organization.